Residential Strategies Towards Mental Health Issues Due To The COVID-19 Global Pandemic - Hasya, Astrini Hadina; Nastiti, Ratna Andriani; Yuanditasari, Aldila (ADBE, 2021)
House is actually a safe and comfortable place for its residents. Moreover, since the COVID-19 outbreak was declared as a global pandemic, especially a national disaster in March 2020, houses in essence and function have become an important concern. Starting from the “stay at home” policy, as much as possible reducing outside activities and even working from home makes peo- ple spend almost all of their time at home. This raises a new problem, the mental health of residents. This paper provides an overview of residential in- terior design strategies to deal with the COVID-19 pandemic by paying atten- tion to the mental health of the occupants. The method used is a literature review by reviewing various literatures and findings in the field. Based on the results of this paper, it is known that there have been changes in aspects and strategies in the interior of the house in adapting to the pandemic to support the physical and mental health of residents.